(untitled) (Fiep Bulletin - online, 2015)
Outdoor adventure sports are embedded in a world of creative imagination, renewing the sense of adventure, interacting directly with risks and uncertainty. In such process of interrelations, while practicing these sports, a person experiences, at once, the pleasure of risk and adventure, unveiling a self-identity that arises the ordinary discourse of a social imaginary that moves alongside death, life, pleasure, pain, reason and emotion. This article intends to unveil the “semantic basin” that bathes the outdoor adventure sports. The corpus of this bibliographical study was built through the approximation of theoretical references that sustain Gilbert Durand’s Theory of the Imaginary (1982, 1988, 1991, 1998, 2001, 2003) and afterwards through national studies relating to outdoor adventure sports, that sustained the creational process of the semantic bay of these sports. The analysis utilizes the six different stages that characterize a semantic basin: drainage, water divisions, confluence, the name of the river, margins and deltas. The semantic basin of outdoor adventure sports rises from the old basins that composes the drainage that allows the river to live up to the myths that build this corporal practice: Dionysius, Hermes, Pan and Narcissus. Key words: social imaginary; outdoor adventure sports; semantic basin.